2004
DOI: 10.1021/pr0499592
|View full text |Cite
|
Sign up to set email alerts
|

Riboproteomics of the Hepatitis C Virus Internal Ribosomal Entry Site

Abstract: Hepatitis C virus (HCV) protein translation is mediated by a cis-acting RNA, an internal ribosomal entry site (IRES), located in the 5′ nontranslated region of the viral RNA. To examine proteins bound to the IRES, which could include proteins important for its function as well as potential drug targets, we used shotgun peptide sequencing to identify proteins in quadruplicate protein affinity extracts of lysed Huh7 cells, obtained using a biotinylated IRES. Twenty-six proteins bound the HCV IRES but not a rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 65 publications
3
56
0
Order By: Relevance
“…Mass spectrometry identified 39 proteins bound to Tob-HCV sORF mRNA. Among others, we found hnRNP C, polypyrimidine tract binding protein 1, and nucleolin, previously described to interact with the HCV 59UTR (Gontarek et al 1999;Ito and Lai 1999;Lu et al 2004). We also identified NF90/NFAR-1, NF45, and RNA helicase A, which interact with both the HCV 59UTR and HCV 39UTR, and function in HCV replication (Isken et al 2007).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Mass spectrometry identified 39 proteins bound to Tob-HCV sORF mRNA. Among others, we found hnRNP C, polypyrimidine tract binding protein 1, and nucleolin, previously described to interact with the HCV 59UTR (Gontarek et al 1999;Ito and Lai 1999;Lu et al 2004). We also identified NF90/NFAR-1, NF45, and RNA helicase A, which interact with both the HCV 59UTR and HCV 39UTR, and function in HCV replication (Isken et al 2007).…”
Section: Resultssupporting
confidence: 66%
“…Interestingly, we also isolated IGF2BP1 that was identified before as an HCV IRES-interacting protein (CRDBP) (Lu et al 2004), but not characterized regarding its function in HCV IRES-mediated translation. A role of IGF2BP1 in the regulation of IGF-II mRNA and b-actin mRNA translation was described before (Nielsen et al 1999;Hüttelmaier et al 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins that remained binding to the RNA under stringent conditions were subsequently analyzed by SDS-PAGE and silver staining and, following extraction and digestion with trypsin, identified by mass spectrometry analysis (see Materials and Methods). Thus, among others, we identified the proteins hnRNP C, polypyrimidine tract binding (PTB) protein, and nucleolin, which were earlier reported to bind to the HCV NTRs (Gontarek et al 1999;Ito and Lai 1999;Lu et al 2004). Most interestingly, we also found the NF/ NFAR proteins NF90/NFAR-1, NF45, and RNA helicase A (RHA) specifically binding to the HCV NTRs (Fig.…”
Section: Nf/nfar Proteins Specifically Bind To the Hcv 59-and 39ntrsupporting
confidence: 53%
“…Several cellular RNA binding proteins have been identified by proteomics that could be involved in this process and in different steps of HCV replication. For instance, 26 host proteins were found to specifically interact with the IRES (Lu et al 2004) and more than 70 cellular factors were identified to interact with the 3 ′ UTR of the plusstrand . Accordingly, it has been speculated that a RNA circularization could be a general replication mechanism for all plus-strand RNA viruses (Herold and Andino 2001).…”
Section: Possible Circularization Of Hcvmentioning
confidence: 99%